The Effect of Electronic Word of Mouth on Food and Beverage Purchase Intentions - Sulestiyoko, Rerry; Bagus Efendi, Muhammad Dafa; Djastuti, Indi (LifeSciFi, 2024)
This study aims to review recent research published between 2014 and 2024 on the impact of Electronic Word of Mouth (e-WOM), a digital marketing strategy on TikTok, on consumers’ purchase intentions for food and beverage products. e-WOM provides consumers with essential information to explore and learn more about these products. Articles were selected based on specific criteria, including open full-text access, publication in reputable international journals ranked Q1 to Q4 on the Scopus Index, and publication within the last decade. From an initial dataset of 69 articles, 52 met the criteria for analysis. The research emphasizes the role of e-WOM in enhancing sales through TikTok's digital marketing platform, providing insights for business owners in the food and beverage industry. Bibliometric methods were employed to identify relevant articles based on titles, abstracts, and keywords. The Scopus database, accessed via the Watase Uake website, was instrumental in gathering relevant publications. Sources included books, theses, conference proceedings, and journal articles written in English. This study highlights the significance of e-WOM in the evolving digital marketing landscape, offering long-term value for entrepreneurs seeking to leverage customer-centric approaches and technological advancements to improve their marketing strategies.